Improve household dietary diversity and food consumption patterns through home garden produce. A capacity building training - Makiso, Markos; Paulos, Tsegayenesh; Ebrahim, Mohammed; Tesfaye, Getachew; Tamene, Lulseged (2024)
This technical report outlines the results of a collaborative work between the Alliance of Bioversity International and CIAT and the Department of Food Science and Postharvest Technology at Wachemo University. The primary objective of this activity was to enhance household dietary diversity, improve food consumption patterns, and strengthen postharvest handling practices. These efforts were undertaken as part of CIAT's integrated home garden intensification work in the Central Ethiopia Peoples Region, specifically focusing on the Doyogena (Adoye cluster) and Lemo (Shurmo cluster) districts under the CGIAR's Mixed Farming System (MFS) initiative. Key activities included an initial assessment of home gardens, baseline measurements of household dietary diversity scores (HDDS) and food consumption scores (FCS), the development of training manuals, and capacity-building sessions for farmers and development agents (DAs). Practical demonstrations and meal planning tailored to local crops significantly enhanced dietary diversity and food security. The HDDS improved from 4-5 to 6-8 food groups per week, and FCS rose from 21.5-35 to an average of 88.5. Lessons learned emphasized the need for continuous follow-up, awareness on postharvest handling, and addressing storage challenges. The project also highlighted opportunities for scaling interventions to improve nutrition, reduce postharvest losses, and enhance livelihoods in the wider community.